Imagining the Growth in Small and Medium Enterprises (SMEs) of Pakistan under COVID19 Outbreak - Ishaq, Arshia; Sadaf, Mamona; Ali, Amjad; Naz, Sehrish (iRASD Journal of Economics, 2022)
Pandemics affect the performance of almost all firms globally. COVID-19, which is considered a pandemic, has disturbed firms worldwide but this impact is more intense on small and medium-sized firms. This study aims to investigate the impact of COVID-19 on the growth performance of majorly export-oriented firms in Pakistan. We surveyed 400 local and exporting firms in Pakistan using random sampling technique. We examined the firm’s growth using the structural equation modeling technique and identified that firm’s finances are not affected much during the pandemic but it has impacted the firm’s operations, supply chains, and labor retention. We further observed that firms ‘efforts in improving their online presence have improved during the pandemic which shows people can change their business strategies according to the changing contingencies. Technology adoption proved one of the dominant strategies for survival under pandemic. We have shared some approaches and policies for curtailing the impact of COVID-19 and improving the firm’s situation.